Economic Research of Electricity Losses in PLN Due to Theft Differences with Methods Changing MCB and Influencing Measurement in kWh Meter - Utomo, Teguh; Ardhenta, Lunde (Faculty of Engineering, Universitas Brawijaya, 2023)
Today, there were many cases of theft or infringement of electricity in various ways. This was caused PLN to suffer losses due to the theft of electricity amounting to Rp 1.5 trillion per year. Electrical theft focused on kWh meter there were various kinds, such as by changing the side of the MCB and adding a needle on the kWh meter. The objective of this study were found out the recorded kWh ratio if the installation was installed normally with a modified installation by changing on the MCB side, adding a needle, and comparing the economic value that PLN should had obtained when the kWh meter was installed normally and the kWh meter was changed. The method used in the research for normal measurement as much as 6 times the rotation of the disk and used 5 variations of load ; the measurement by changing the MCB and adding the needle was the same as the normal measurement, only when changing the MCB changes 2 A to 4 A, and when adding the needle, the disk was plugged with a needle. The result showed that the average of error difference between kWh meter that was installed normally with that has been changed on the side of MCB is 0, and kWh meter installed with normal that has been changed add needle equal to -44.1586. The difference in total cost of electricity for one month for normal kWh meter with which has been changed on the MCB side was Rp. 165.914.-, and for the normal kWh meter difference with the added needle of Rp. 58.610.